Pengaruh Kompensasi Dan Work Family Conflict Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening - Moch Rizqy Mubarok; Ikhsan Maksum (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the effect of compensation and work family conflict on employee performance, with job satisfaction as an intervening variable. Human resources (HR) are a strategic asset of an organization, so understanding the factors that influence employee performance is very important. By identifying these factors, companies can formulate more effective HR policies. The research approach used is quantitative. The object of the study was employees of the Public Relations division of PT Demang Jaya. Data were collected through questionnaires and analyzed using SmartPLS 4 (PLS-SEM). The results of the analysis showed that compensation had a positive and significant effect on employee performance, while work-family conflict did not have a significant effect on employee performance. In addition, job satisfaction mediated the relationship between compensation and employee performance, but did not mediate the effect of work-family conflict on employee performance. These findings emphasize the need for companies to improve competitive compensation policies in order to encourage employee performance and job satisfaction.